Efektivitas Penerapan Project Based Learning Terhadap Hasil Pembelajaran dan Motivasi Siswa [Effectiveness of Project Based Learning Implementation on Student Learning Outcomes and Motivation] - Marina, Indra; Seda, Fredrikus; Hardiono, Dwi (Jurnal Teropong Pendidikan, 2024)
The development of digital technology has influenced various fields, including education. One learning model that can utilize technology is Project-Based Learning (PBL). The purpose of this study is to provide empirical evidence to support the implementation of PBL as an effective learning strategy, improve the quality of learning, and provide meaningful learning experiences for students. Using simple regression analysis and involving 51 students, the results of the study show a moderate positive correlation between the level of PBL implementation and student learning outcomes. The regression equation confirms that PBL not only improves learning outcomes but also significantly impacts student motivation. Recommendations include widespread implementation of PBL, teacher training, development of relevant PBL projects, as well as continuous monitoring and evaluation. Further research is needed to generalize these findings to a broader educational context.